Playing Cards on Asthma Management: A New Interactive Method for Knowledge Transfer to Primary Care Physicians - Louis-Philippe Boulet; Francine Borduas; Jacques Bouchard; Johanne Blais; Frederick E Hargreave; Michel Rouleau (Canadian Respiratory Journal)
OBJECTIVES: To describe an interactive playing card workshop in the communication of asthma guidelines recommendations, and to assess the initial evaluation of this educational tool by family physicians.